2009
DOI: 10.26719/2009.15.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum zinc deficiency in cases of neural tube defect in Gorgan, north Islamic Republic of Iran

Abstract: Previous studies have shown a high rate of neural tube defects (NTD) in Gorgan, northern Islamic Republic of Iran. This case-control study during 2003-04 compared serum zinc levels and other variables in 23 mothers of neonates affected with NTD and 36 mothers with normal healthy neonates in Dezyani hospital in Gorgan. Mean serum zinc levels in the case and control groups were 13.43 µmol/L (SD 6.3) and 11.41 µmol/L (SD 6.3) respectively. Zinc deficiency was found in 13 (36.5%) of the cases and 7 (19.4%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Zinc deficiency has been widely reported to be associated with NTD risk (Carrillo‐Ponce Mde et al, ; Golalipour et al, ; Dey et al, ). Because the hair Zn concentration in this population was at a comparable level to previous studies (Chojnacka et al, ; Wu et al, ; Gellein et al, ; Hsieh et al, ), we considered that there was no Zn deficiency in study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency has been widely reported to be associated with NTD risk (Carrillo‐Ponce Mde et al, ; Golalipour et al, ; Dey et al, ). Because the hair Zn concentration in this population was at a comparable level to previous studies (Chojnacka et al, ; Wu et al, ; Gellein et al, ; Hsieh et al, ), we considered that there was no Zn deficiency in study participants.…”
Section: Discussionmentioning
confidence: 99%
“…reported a maternal low serum zinc level and a high copper level as an association with NTDs (8). A recent study in Iran reported maternal zinc deficiency to be associated with NTDs (21). However, results of some studies also suggest that zinc deficiency was not related to NTDs (22,23), although population-based case-control studies concluded that the risk of NTDs in infants and foetuses decreased with increasing maternal zinc intake (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…S1). The epidemiology data highlight that lower zinc levels in maternal or fetal tissues are associated with NTDs in Turkey (Çavdar et al, 1991Cengiz et al, 2004;Demir et al, 2017;Zeyrek et al, 2009), Iran (Golalipour et al, 2009), China (Yan et al, 2017), Netherlands (Groenen et al, 2003), England (Buamah et al, 1984;Hinks et al, 1989;Leger et al, 1980), Bangladesh (Dey et al, 2010), Mexico (Carrillo-Ponce Mde et al, 2004) and India (Srinivas et al, 2001) (blue frames in Fig. S1).…”
Section: Introductionmentioning
confidence: 99%